1984
DOI: 10.1172/jci111598
|View full text |Cite
|
Sign up to set email alerts
|

Differential acute effects of aldosterone, dexamethasone, and hyperkalemia on distal tubular potassium secretion in the rat kidney.

Abstract: Abstract. To determine the specific effects on renal potassium transport of acute elevations in plasma aldosterone, dexamethasone, and potassium concentrations, we studied adrenalectomized rats prepared such that each factor could be varied independently. Clearance data alone could not be used to deduce the underlying tubular transport effects, however, since infusion of each of these agents was associated with a marked change in urinary flow rate, which may itself have influenced potassium excretion. We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 41 publications
10
75
1
Order By: Relevance
“…Young and Paulsen stressed the powerful effect of increased plasma K + levels on renal K + excretion.25 years ago. 39 However, although elevation of plasma K + concentrations by intravenous K + infusions increases apical K + conductances in distal tubules, 23,57 reduces NCC phosphorylation, and drives kaliuresis, 58 ex vivo studies on mouse CD cells and isolated renal tubules failed to detect any significant direct effects of increased extracellular K + concentrations on ENaC and ROMK channel activities 59 and NCC phosphorylation. 35 In summary, AS 2/2 mice adapt to physiologically relevant challenges in dietary K + intake without major signs of illnesses and hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Young and Paulsen stressed the powerful effect of increased plasma K + levels on renal K + excretion.25 years ago. 39 However, although elevation of plasma K + concentrations by intravenous K + infusions increases apical K + conductances in distal tubules, 23,57 reduces NCC phosphorylation, and drives kaliuresis, 58 ex vivo studies on mouse CD cells and isolated renal tubules failed to detect any significant direct effects of increased extracellular K + concentrations on ENaC and ROMK channel activities 59 and NCC phosphorylation. 35 In summary, AS 2/2 mice adapt to physiologically relevant challenges in dietary K + intake without major signs of illnesses and hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the rabbits were maintained on glucocorticoid replacement therapy (dexamethasone 10 pg/kg s.c.) from the second postoperative day until death ( 12-15 d). This dose ofglucocorticoid minimizes mineralocorticoid activity, while enhancing food and water intake as well as the general well-being of the animals (18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%
“…K secretion is regulated by hormones such as vasopressin (1,2,8) and aldosterone and dietary K intake (11,12,26,34). A large body of evidence has demonstrated that a low-K intake decreases, whereas a high-K intake increases renal K secretion (3,4,13,24).…”
mentioning
confidence: 99%